MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI MODEL PEMBELAJARAN MAKE A MATCH ANAK USIA 4-5 TAHUN DI PAUD TUNAS JAYA DESA PETAPAHAN JAYA KECAMATAN TAPUNG - Sity Lutfiah; Zulirfan Zulirfan; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase ability to know the numbers emblem in children aged 4-5 years through learning models make a match in early childhood Tunas Jaya Jaya subdistrict Tapung Petapahan village. This study is je nis studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are children aged 4-5 years are numbered 20 children in Tunas Jaya , The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. Ha sil research shows that learning model make a match can improve ability to know the numbers emblem in children aged 4-5 year. It Dapa t be seen from the increase in the average percentage of the ability to know the symbol of the numbers in the first cycle of 53.65%, which is at a fairly high category and an increase of 51.97% in the second cycle to 81, 5 3% are located in either category. So, make a match the learning model can improve the ability to know the symbol of the number of children aged 4-5 years in early childhood Tunas Jaya Jaya subdistrict Tapung Petapahan village.Keywords : Know Your Numbers Coat ability, Learning Model Make A Match